Consequence of Covid-19 lockdown on household food security: Voices from Hoima City, Uganda - David Mwesigwa (Journal of Social, Humanity, and Education, 2021)
Purpose: To investigate the consequence covid-19 lockdown on food security among a cohort of peri-urban households in Hoima city. Research methodology: A descriptive survey was employed targeting 186 respondents. Data were collected using a researcher-designed self-administered questionnaire and analysed using quantitative statistics. Specifically, chi-square was employed to establish whether the hypothesis held sway; also, regression analysis was employed with a view of forecasting the degree of change in household food security due to covid-19 lockdown. Results: The period of lockdown announced and implemented by the government had a positive consequence on food security. Nonetheless, the economic hardships overturned the successes otherwise achieved as a number of households sold off much of the food so as acquire other household items. Recommendations: While the government is credited for instituting a lockdown as a means to reduce the spread of covid-19 virus, it is recommended that city authorities are encouraged to boost urban farming by distributing agri-inputs to households in the peri-urban seeing that their daily incomes are already constrained. Contribution: The findings of this study may be useful to city authorities in Uganda in evolving a guide on integration of food security as a cross-cutting issue in the overall strategic disaster management plan. This article makes an input to the budding field of understanding by underlining inroads that can generate more sustainable urban community livelihoods through food security.